2015
DOI: 10.1099/jmm.0.000177
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian antimicrobial peptide fallaxin analogue FL9 affects virulence gene expression and DNA replication in Staphylococcus aureus

Abstract: The rapid rise in antibiotic-resistant pathogens is causing increased health concerns, and consequently there is an urgent need for novel antimicrobial agents. Antimicrobial peptides (AMPs), which have been isolated from a wide range of organisms, represent a very promising class of novel antimicrobials. In the present study, the analogue FL9, based on the amphibian AMP fallaxin, was studied to elucidate its mode of action and antibacterial activity against the human pathogen Staphylococcus aureus. Our data sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Then, AMPs can destroy the cell envelope and effectively induce a leakage of cytosol (Huang et al, 2010). It has been proven in our study that ID13 had the ability to destroy the cell envelope and cause K + or other contents to release extracellularly (Figures 4, 6), and then bound to intracellular target gDNA and destroyed its helical structure (Figure 5), which might result in the inhibition of DNA synthesis (Gottschalk et al, 2015). In contrast, DLP4 showed less potent damage to cell membrane than that of ID13 (Figures 4, 6), but it showed stronger binding ability to S. aureus gDNA (Figure 5), which might attribute to its less α-helix content in bacterial membrane mimicking conditions and more net positive charges.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Then, AMPs can destroy the cell envelope and effectively induce a leakage of cytosol (Huang et al, 2010). It has been proven in our study that ID13 had the ability to destroy the cell envelope and cause K + or other contents to release extracellularly (Figures 4, 6), and then bound to intracellular target gDNA and destroyed its helical structure (Figure 5), which might result in the inhibition of DNA synthesis (Gottschalk et al, 2015). In contrast, DLP4 showed less potent damage to cell membrane than that of ID13 (Figures 4, 6), but it showed stronger binding ability to S. aureus gDNA (Figure 5), which might attribute to its less α-helix content in bacterial membrane mimicking conditions and more net positive charges.…”
Section: Discussionmentioning
confidence: 74%
“…Antibiotics play pivotal roles in disease prevention, growth promotion, and production improvement in animal husbandry (Ferber, 2002;Cheng et al, 2014;Van Boeckel et al, 2015). Nevertheless, the long-term use of antibiotics in animal breeding can accelerate the emergence of antibiotic-resistant bacteria (ARB), including Staphylococcus aureus, which can cause trauma infection, abscess, cellulitis, mastitis, endometritis, arthritis, septicemia, and sepsis in animals (Fluit, 2012;Foster, 2012;Dan et al, 2019). It has been found that S. aureus is resistant to tetracycline, methicillin, erythromycin, clindamycin, ciprofloxacin, and vancomycin (Hiramatsu, 2001;Lai et al, 2018;Pirolo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular mechanism underlying Enterococcus resistance to L12 requires further investigation in future studies. The MIC of L12 against S. aureus was similar to traditional antibacterial drugs, and the antibacterial activity of L12 was comparable with other AMPs (22)(23)(24)(25). Furthermore, the MICs of L12 exhibited no correlation with resistance to the tested antibiotics, the strains resistant to more antibiotics were not more resistant to L12, which suggested that L12 may be used to treat infections caused by MRSA strains.…”
Section: Discussionmentioning
confidence: 83%
“…It was also shown that peptides taken at subinhibitory concentrations induce an SOS response of bacterial cells. Finally, we demonstrated the killing effect of indolicidin, and its analogue was realized because of the disturbance of the bacterial cell wall, while the interaction with intracellular DNA may lead to other effects; for example, to affecting of expression of some genes .…”
Section: Resultsmentioning
confidence: 94%